Association of Fruit and Vegetable Intake and Physical Activity with Primary Dysmenorrhea among Centrally Obese Adolescents - Febi Febriana Kusnaidi; Vitri Widyaningsih; Intan Suraya Ellyas (GLOBAL HEALTH SCIENCE GROUP, 2026)
Primary dysmenorrhea is a common reproductive health issue among female adolescents and is closely linked to lifestyle factors, including dietary patterns and physical activity, particularly among those with central obesity. This study aims to analyze the relationship between fruit and vegetable consumption, exercise habits, and primary dysmenorrhea among adolescents with central obesity. An analytical observational study with a cross-sectional design was conducted in February 2026 across four public senior high schools in Surakarta. A sample of 128 centrally obese female students was selected using multistage sampling. Data were collected via interviews using a standardized FFQ, a validated 12-item exercise habits questionnaire (Pearson's r > 0.804; Cronbach's alpha = 0.970), and a standardized NRS. Data were analyzed using statistical software through univariate and bivariate analyses (p < 0.05). The majority of respondents reported irregular fruit and vegetable consumption (56.3%) and irregular exercise habits (55.5%), and most experienced moderate-to-severe dysmenorrhea. Statistically significant relationships were found between fruit and vegetable consumption and dysmenorrhea (p = 0.004) and between exercise habits and dysmenorrhea (p < 0.001). Irregular consumption and low physical activity were strongly associated with higher pain severity. Fruit and vegetable consumption and exercise habits are significantly associated with the severity of primary dysmenorrhea among adolescents with central obesity. Promoting healthy dietary habits and regular physical activity may mitigate the severity of dysmenorrhea in this population.